Spontaneous Self-Organization Enables Dielectrophoresis of Small Nanoparticles - Jung, Seung-Ho (2011)
[Image: see text] Detailed understanding of the mechanism of dielectrophoresis (DEP) and the drastic improvement of its efficiency for small size quantized nanoparticles (NPs) open the door for the convergence of microscale and nanoscale technologies. It was hindered however by the severe reduction of DEP force in particles with volume below few hundred nm(3). We report here DEP assembly of size quantized CdTe nanoparticles (NPs) with a diameter of 4.2 nm under AC voltage of 4–10 V. Calculations of the nominal DEP force for these NPs indicate that it is several orders of magnitude smaller than the force of the Brownian motion destroying the assemblies even for the maximum applied AC voltage. Despite this theoretical background, very efficient formation of NP bridges between electrodes separated by a gap of 2μ was observed even for AC voltages of 6V and highly dilutes NP dispersions. The resolution of this conundrum was found in the intrinsic ability of CdTe NPs to self-assemble. The species being assembled by DEP are substantially bigger than the individual NPs. DEP assembly should be treated as a process taking place for NP chains with a length of ca 140 nm. The self-assembled chains increase the nominal volume where the polarization of the particles takes place, while retaining the size-quantized nature of the material. The produced NP bridges were found to be photoactive producing photocurrent upon illumination. DEP bridges of quantum confined NPs can be used in fast parallel manufacturing of novel MEMS components, sensors, optical, and optoelectronic devices. Purposeful engineering of self-assembling properties of NPs makes possible further facilitation of the DEP assemblies and increase of complexity of the produced nano- and microscale structures.